The Determinant Factors of E-Commerce Purchase Decision in Jakarta and Tangerang - Arby Virto Gunawan; Linawati Linawati; Dimas Pranandito; Rano Kartono (Bina Nusantara University, 2019)
This research aimed to identify the factors that influenced the purchase decision in e-commerce. These used factors were brand image, price, and trust which were adopted from the previous research. The research was designed using a quantitative method with accidental sampling. From 200 questionnaires, there were 117 returned questionnaires from respondents who had made online purchases around Jakarta and Tangerang. The data was analyzed using SPSS. The result shows that brand image has positive influences on purchase decision. On the other hand, price and trust do not influence it. Price is the secondary commitment to make a purchase decision. Thus, a lower price does not guarantee the convenience of online shopping. Meanwhile, trust in making online decisions are built from brand image, shop, and strong products in the market place. Those rejected variables are affected by research fields and target samples.